2016
DOI: 10.1038/ismej.2016.131
|View full text |Cite
|
Sign up to set email alerts
|

Fungal–bacterial dynamics and their contribution to terrigenous carbon turnover in relation to organic matter quality

Abstract: Ecological functions of fungal and bacterial decomposers vary with environmental conditions. However, the response of these decomposers to particulate organic matter (POM) quality, which varies widely in aquatic ecosystems, remains poorly understood. Here we investigated how POM pools of substrates of different qualities determine the relative contributions of aquatic fungi and bacteria to terrigenous carbon (C) turnover. To this end, surface sediments were incubated with different POM pools of algae and/or le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(74 citation statements)
references
References 57 publications
1
73
0
Order By: Relevance
“…The strong effect of temperature on the rate of soil C mineralization does not rule out the importance of soil microbial community, as it is recognized that climate and environmental factors can mask the influence of decomposer community on decomposition, due to the fact that soil microorganisms may both adapt to and be affected by climate and environments (Canarini, Carrillo, Mariotte, Ingram, & Dijkstra, 2016; Keiser & Bradford, 2017). Moreover, the structure and functions of soil microbial communities are further constrained by soil physiochemical properties and SOM quality (Fabian, Zlatanovic, Mutz, & Premke, 2017; Sun et al., 2016; Xun et al., 2015; You et al., 2014, 2016). Growing evidences show that soil geochemistry and physical structure impose direct effects on SOM stability by creating physiochemical barriers preventing microorganisms to access carbon sources (Bardgett et al., 2008; Chenu & Plante, 2006; Delgado‐Baquerizo et al., 2015; Doetterl et al., 2015; Plante, Conant, Stewart, Paustian, & Six, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The strong effect of temperature on the rate of soil C mineralization does not rule out the importance of soil microbial community, as it is recognized that climate and environmental factors can mask the influence of decomposer community on decomposition, due to the fact that soil microorganisms may both adapt to and be affected by climate and environments (Canarini, Carrillo, Mariotte, Ingram, & Dijkstra, 2016; Keiser & Bradford, 2017). Moreover, the structure and functions of soil microbial communities are further constrained by soil physiochemical properties and SOM quality (Fabian, Zlatanovic, Mutz, & Premke, 2017; Sun et al., 2016; Xun et al., 2015; You et al., 2014, 2016). Growing evidences show that soil geochemistry and physical structure impose direct effects on SOM stability by creating physiochemical barriers preventing microorganisms to access carbon sources (Bardgett et al., 2008; Chenu & Plante, 2006; Delgado‐Baquerizo et al., 2015; Doetterl et al., 2015; Plante, Conant, Stewart, Paustian, & Six, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For the latter, it has been shown that the reduction of soil moisture can limit enzyme and substrate diffusion (Liu, Zhang, & Wan, 2009) and enzyme efficiencies could be affected, possibly because processes such as enzyme immobilisation are increased while diffusion rates are reduced (Henry, 2013). Fabian, Zlatanovic, Mutz, and Premke (2017) showed that the use of recalcitrant carbon compounds would be F I G U R E 5 Relationships between water content and extracellular polymeric substances (log EPS), bacterial viability (log Live cells), βd-xylosidase (log XYL) and βd-glucosidase (log GLU). Fabian, Zlatanovic, Mutz, and Premke (2017) showed that the use of recalcitrant carbon compounds would be F I G U R E 5 Relationships between water content and extracellular polymeric substances (log EPS), bacterial viability (log Live cells), βd-xylosidase (log XYL) and βd-glucosidase (log GLU).…”
Section: Long-term Drought Effects In Surface and Hyporheic Sedimentsmentioning
confidence: 99%
“…Stable isotope analysis of the respired CO 2 provides information on carbon substrates metabolized by the microbial community (Fabian et al, 2017). The ratio of 13 С/ 12 С in the dissolved CO 2 was measured directly in each microcosm by a membrane-inlet mass-spectrometer dissolved gas analyser (HiCube pumping station, Pfeiffer Vacuum and Bay Instruments membrane, USA), controlled by Quickdata software.…”
Section: Carbon Stable Isotope Ratiomentioning
confidence: 99%